Evaluasi Kinerja Pusat Koperasi Produsen Tempe Tahu Indonesia (PUSKOPTI) di Provinsi Jawa Barat dan Strategi Peningkatannya - Hugo Siswaya; Trida Gunadi; Suarny Amran (J-Coop : Journal of Co-operative, 2025)
This dissertation evaluates the performance of the Indonesian Producer Cooperative Center for Tempe Tahu (Puskopti) in West Java and proposes strategic improvements. The study focuses on assessing both financial and non-financial aspects of Puskopti’s operations through a balanced scorecard framework. Despite facing various challenges including limited resources and inadequate innovation, Puskopti demonstrates strong potential in enhancing its services and products to meet evolving consumer demands. Key findings indicate that while financial ratios show satisfactory levels of liquidity and solvability, profitability remains a concern due to inefficient resource allocation. Additionally, customer satisfaction rates are relatively high, although retaining current membership and attracting new ones poses ongoing issues. Furthermore, internal processes require optimization particularly regarding innovative product development and diversified business activities. Lastly, capacity-building efforts among members via regular training sessions could significantly enhance overall efficiency. By addressing these shortcomings strategically, this evaluation aims to bolster Puskopti’s sustainability and reinforce its role in promoting local economic development.